Komodifikasi Agama dalam Ruang Politik di Seberang Kota Jambi - Batubara, Ariyandi; Malik, Abdul (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
Religion in an ideal concept was understood as guide measure of moral. Religion was the way of life that had doctrines with universal meanings and cross the space and Â time along with always relevant to be directived in all context, including politic. But this perspectives on the real situation was deviate. So, today, religion was shifted from its position as guidliness become only instrument and could be understood with flexible according to person comprehension who exploitation the religion itself. This research wanted to find the answer (1) what was the motivation of religion put into politic space on Seberang Kota Jambi, (2) how did the kinds of religion commodification in politic space on Seberang Kota Jambi, and (3) what was the implication from the religion commodification phenomenon in politic space on Seberang Kota Jambi. By using the data that took from observation, interview, and documentation, this research found (1) the motivation of majority politicans on Seberang Kota Jambi put religion into politic pace was to get a power, (2) and the forms of religion commodofication in politic space on Seberang Kota Jambi were using Kitab YÄsÄ«n as politic promotion, put religion symbols into politic banner, and using ulama as instrument for increasing politic electability, etc. If this phenomenon allowed as well as, so in future time would bring (3) implication in understanding of religion become superficial and partial. This research was recomended to stakeholders as politicans, ulama, academics, and people of Seberang Kota Jambi to take their own part, so that religioncould be understood and done.